GABAB Receptor Signaling in the Dorsal Motor Nucleus of the Vagus Stimulates Gastric Motility via a Cholinergic Pathway - Cruz, Maureen T.; Dezfuli, Ghazaul; Murphy, Erin C.; Vicini, Stefano; Sahibzada, Niaz; Gillis, Richard A. (Frontiers in Neuroscience, 2019)
Central nervous system regulation of the gastric tone and motility is primarily mediated via preganglionic neurons of the dorsal motor nucleus of the vagus (DMV). This is thought to occur by simultaneous engagement of both independent excitatory and inhibitory pathways from the DMV and has been proposed to underlie the opposing effects seen on gastric tone and motility in a number of in vivo models. Contrary to this view, we have been unable to find any evidence for this 'dual effector' pathway. Since this possibility is so fundamental to how the brain-gut axis may interact in light of both peripheral and central demands, we decided to explore it further in two separate animal models previously used in conjunction with GABAB signaling to report the existence of a 'dual effector' pathway. Using anesthetized rats or ferrets, we microinjected baclofen (7.5pmol; n=6), a GABAB agonist into the DMV of rats or intravenously administered it (0.5mg/kg; n=4) in ferrets. In rats, unilateral microinjection of baclofen into the DMV caused a robust dose-dependent increase in gastric tone and motility that was abolished by ipsilateral vagotomy and counteracted by pre-treatment with atropine (0.1mg/kg; IV). Similarly, as microinjection in the rats, IV administration of baclofen (0.5mg/kg) in the ferrets induced its characteristic excitatory effects on gastric tone and motility, which were blocked by either pre- or post-treatment with atropine (0.1mg/kg; IV). Altogether, our data provide evidence that the gastric musculature (other than the gastric sphincters) is regulated by a 'single effector' DMV pathway using acetylcholine.